Biomonitoring of PAHs by using Quercus ilex leaves: Source diagnostic and toxicity assessment - De Nicola, Flavia; Claudia, Lancellotti; MariaVittoria, Prati; Giulia, Maisto; Anna, Alfani (Atmospheric Environment, 2011)
Quercus ilex L. leaves were sampled at nineteen urban sites and two remote sites in order to evaluate PAH contamination degree. One-, two- and three-year-old leaves were collected and leaf lipid content was measured to investigate the inﬂuence of leaf age and lipids in PAH accumulation. Some PAH diagnostic ratios, such as Ant/Ant þ Phen, Flt/Flt þ Pyr, B[a]A/B[a]A þ Crys and IP/IP þ B[g,h,i]P, were calculated. The results suggest that Q. ilex leaves are effective biomonitors of PAH air contamination: in fact, a great PAH accumulation in leaves from the urban areas, until 30-time higher compared to those from the remote sites, has been observed. At each site, the similar total PAH concentrations in leaves of different age, probably due to a canopy effect, indicate an ability of all leaf age classes to monitor local PAH concentrations in air, remarking practical implications for air biomonitoring. The ﬁndings suggest that PAH adsorption in Q. ilex leaves does not result limited by leaf lipid content. Moreover, this study demonstrates the source-diagnostic potential of Q. ilex leaves, because, in particular, the Flt/Flt þ Pyr and IP/ IP þ B[g,h,i]P ratios indicate vehicular trafﬁc as the main source of PAHs in the urban areas and wood combustion in the remote areas. Moreover, to distinguish biomass combustion source, a promising tracer PAH as DB[a,h]A could be used. The high contribution of DB[a,h]A to total PAH concentrations at the remote sites determines a high carcinogenic potential in this area, similar to that calculated for the urban area where the carcinogenic PAH concentrations in absolute values are often higher.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Carcinogenic PAH; leaf age; Leaf dry weight; Leaf lipid; PAH diagnostic ratio; Toxic equivalent factor